China’s accession to the WTO and its impact on global agricultural trade - Glauber, Joseph W. (International Food Policy Research Institute, 2021)
China’s rapid rise as a leading global exporter of manufacturing goods since its accession to the WTO in 2001 has been the focus of both admiration and, increasingly, concern, but China is also a large importer of goods, particularly agricultural products. Since China's accession to the WTO, China agricultural exports have increased by 8 percent annually while imports have risen by almost twice that rate. China has become the world's largest importer of agricultural products and the first or second largest destination for many of the world's top agricultural exporters such as the US, Brazil, Australia, New Zealand, Canada and Argentina. This paper examines the evolution of China's agricultural trade since accession and discusses how agricultural trade and domestic support policies have evolved, with particularly emphasis on China's experience as complainant and respondent in WTO trade disputes.